Bad and Good Faith of the Applicant in the Restitution Process: The Case-Law of the ECtHR - Bruskina, Nika (Teisė, 2018)
[full article, abstract in Lithuanian; only abstract in English] The Article examines the case-law of the ECtHR related to the good or bad faith of the applicant in the context of the restoration of ownership rights to the property nationalized in the past.